The DETAIL questionnaire is a useful and effective tool to assess spondyloarthritis in patients with inflammatory bowel disease - Keskin, Onur; Farisogullari, Bayram; Yardimci, Gozde Kubra; Gurbuz, Burcu; Kole, Melike; Parlak, Erkan; Karadag, Omer; Kav, Taylan; Kalyoncu, Umut (Frontiers in Medicine, 2023)
Introduction:This study aimed to determine how many patients with IBD could be diagnosed with spondyloarthropathy (SpA) by applying a simple questionnaire related to the musculoskeletal system. Material-Methods: A musculoskeletal symptom questionnaire was given to all patients with IBD during their follow-up examinations between January 2020 and November 2021. The DETAIL questionnaire consisting of six questions about the musculoskeletal system was administered by asking the patients with IBD. All patients who answered yes to at least one of these questions were directed to specialists in the rheumatology department to undergo a detailed examination. The patients who were diagnosed with rheumatological disease after further investigation were recorded. Patients with a known diagnosis of rheumatological disease were excluded from the study. Findings:There were 333 patients with IBD included in the study. Of these patients, 41 (12.3%) had a previously diagnosed rheumatological disease and were excluded from the evaluation. Of the remaining 292 patients (147 with ulcerative colitis, 139 with Crohn’s disease and 6 with indeterminate colitis; mean age 42 years), 67 (23%) answered yes to at least one of the questions and were referred to a rheumatology consultation. Rheumatological examination was completed in 52 patients. As a result of the evaluations, 24 patients (8.2%) were diagnosed with enteropathic arthritis (14 axial, 9 peripheral and 1 axial plus peripheral). Patients with newly diagnosed enteropathy had a lower median disease age than patients without enteropathy. Conclusion: The DETAIL questionnaire is an effective and easy tool for identifying missed cases of SpA in patients with IBD.